2019
DOI: 10.1111/btp.12648
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of waterbird assembly mechanisms revealed by patterns in phylogenetic and functional diversity in a subtropical wetland

Abstract: Despite growing interest in using phylogenetic and functional methods to understand community assembly, few studies have examined how these methods can be used to assess seasonal variation in assembly mechanisms among migrant species.Migration can rapidly alter the relative influence of stochastic processes, species interactions, or environmental factors in shaping communities across seasons. Here, we describe seasonal dynamics in the phylogenetic and functional diversity of waterbirds in Mai Po Wetland, a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Environmental filtering would result in negative SESFRic and SESFDis values by allowing only a set of species with certain functional traits to persist and by forcing most of the biomass into a small trait space (Liu, Swenson, Zhang, & Ma, 2013; Mason et al., 2005). These findings were also in concordance with some of the previous studies on waterbirds that reported functionally clustered waterbirds communities (the western populations in Che et al., 2018; summer season in Che et al., 2019; Li et al., 2019). For organisms like waterbirds, which have high‐dispersal capabilities and can respond to changes in the environment quickly, priority effects (Chase, 2003) and stochastic processes (Hubbell, 2001) are less likely to be dominant players in community assembly (Daniel et al., 2019; Fukami, 2015; Li et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Environmental filtering would result in negative SESFRic and SESFDis values by allowing only a set of species with certain functional traits to persist and by forcing most of the biomass into a small trait space (Liu, Swenson, Zhang, & Ma, 2013; Mason et al., 2005). These findings were also in concordance with some of the previous studies on waterbirds that reported functionally clustered waterbirds communities (the western populations in Che et al., 2018; summer season in Che et al., 2019; Li et al., 2019). For organisms like waterbirds, which have high‐dispersal capabilities and can respond to changes in the environment quickly, priority effects (Chase, 2003) and stochastic processes (Hubbell, 2001) are less likely to be dominant players in community assembly (Daniel et al., 2019; Fukami, 2015; Li et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in permanent and large lakes such as our study lakes, environmental filtering is expected to be more prominent in community assembly as compared to smaller and temporary wetlands, where stochastic events and priority effect are expected to be major determinants of assembly (Daniel et al., 2019; Li et al., 2019). However, it should also be noted that there have been other studies reporting neutrally assembled waterbird communities (spring and autumn populations in Che et al., 2019; populations of temporary wetlands in Daniel et al., 2019; de Arruda Almeida et al., 2019) and functionally over‐dispersed waterbird communities (the eastern populations in Che et al., 2018; winter populations in Che et al., 2019). Overall, various factors including climate, wetland age, wetland size, season of the year, population densities, and trophic states of wetlands seem to be capable of influencing waterbird community assembly.…”
Section: Discussionmentioning
confidence: 97%
“…The lowest abundance during the rainy season, when most birds breed, is possibly due to reproductive displacement (Sick 1997). Indeed, Ardeidae offspring frequently disperses locally after maturation (Che et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As previously well-documented, seasonality (Caula et al, 2008;Chen et al, 2019;Gomes et al, 2017;Girma et al, 2017;Katuwal et al, 2016) and habitat (Caula et al, 2008;Chen et al, 2018;Chen et al, 2019;Durmuş et al, 2018;Girma et al, 2017) influence the species richness and population size. The present results of the study are consistent with the previous reports given above.…”
Section: Fig 2 Bird Population Density Graph On Akdoğan Lakementioning
confidence: 72%